Diagnosing Poor Performance and Enhancing Motivation of Employees - Adhikari, Kamal Prakash (Management Dynamics, 2018)
This study attempts to examine the diagnosing poor performance and enhancing motivating employees in the banks in Kathmandu City. Major objective of the research is to identify the causes of poor performance in banks employee to motivate them. Fourty human resource managers of the banks are the sample of the study. Structured questionnaires were used to collect data. Descriptive statistics and regression analysis is used for data analysis purpose. It was found equitable rewards system, using internal and external incentives, facilitating performance, and linking performance to rewards and discipline are the major factors for diagnosing performance of employees in the banks.